2019
DOI: 10.1111/liv.14323
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal studies can identify distinct inflammatory cytokines associated with the inhibition or progression of liver cancer

Abstract: Abbreviations: CD, chow diet; DIAMOND, diet-induced animal model of nonalcoholic fatty liver disease; HCC, hepatocellular carcinoma; NAFLD, nonalcoholic fatty liver disease; NASH, nonalcoholic steatohepatitis; WD, Western diet. AbstractBackground and Aims: Chronic diseases such as nonalcoholic fatty liver disease (NAFLD) and hepatocellular carcinoma (HCC) are associated with chronic inflammation. However, controversial reports as to the key cytokines involved in the process of chronic inflammation hinder devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…cxcl11 . 6 is homologous to human cxcl9 , which was shown to be upregulated in patients with NAFLD and associated with the promotion of the progression of NAFLD to hepatocellular carcinoma ( 109, 110 ). It is tempting to speculate that cxcl11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…cxcl11 . 6 is homologous to human cxcl9 , which was shown to be upregulated in patients with NAFLD and associated with the promotion of the progression of NAFLD to hepatocellular carcinoma ( 109, 110 ). It is tempting to speculate that cxcl11 .…”
Section: Discussionmentioning
confidence: 99%
“…cxcl11.6/dpp4 showed specifically high activity between inflammatory macrophages and hepatocytes. cxcl11.6 is homologous to human cxcl9, which was shown to be upregulated in patients with NAFLD and associated with the promotion of the progression of NAFLD to hepatocellular carcinoma (109,110). It is tempting to speculate that cxcl11.6 may be considered a candidate gene for studying the inflammatory response of inflammatory macrophages and hepatocytes in the context of NAFLD in a zebrafish model.…”
Section: Discussionmentioning
confidence: 99%
“…The expression level of CXCR2 in HCC was significantly higher than normal liver tissues, and the expression levels of CXCR2 mRNA and protein were associated with intrahepatic metastasis, portal vein tumor thrombus, and poor differentiation ( 26 ). A longitudinal study has indicated that the chronically increasing trend of CXCL5 were associated with the promotion of the progression of NAFLD to HCC in males ( 27 ). Xu’s study had shown that overexpression of CXCL5 in HCC cells has higher metastatic potential, which also demonstrated that CXCL5/CXCR2 and ERK1/2 highway may play an important role in the migration of HCC ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, no further reports have been made on the role of mCCL12 in liver disease, with the exception of a longitudinal analysis that found that male mice, a chronically increasing trend in mCCL12 was associated with the progression of NAFLD to HCC (30). However, based on the high homology of mCCL12 with the human CCL2 protein (68%), mCCL12 may also play an essential role in liver pathology, which needs to be confirmed by further studies.…”
Section: Ccl12 In Liver Diseasementioning
confidence: 97%